2010
DOI: 10.1016/j.ejrad.2008.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 64 multislice CT angiography in the assessment of coronary in-stent restenosis: A meta-analysis

Abstract: Our results showed that 64-slice CT angiography has high diagnostic value (both sensitivity and specificity) for detection of coronary in-stent restenosis based on assessable segments when compared to conventional coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 39 publications
3
58
1
5
Order By: Relevance
“…The diagnostic accuracy of post-stent CCTA hovers between 90 and 91%. 5 Our study also revealed similar efficacy of CCTA for confirming stent patency or thrombosis.…”
Section: Discussionsupporting
confidence: 77%
“…The diagnostic accuracy of post-stent CCTA hovers between 90 and 91%. 5 Our study also revealed similar efficacy of CCTA for confirming stent patency or thrombosis.…”
Section: Discussionsupporting
confidence: 77%
“…evaluated the benefit of MS-CT in the detection of the coronary in-stent restenoses in their metaanalyses (nearly 1400 and 1500 evaluated stents). In these metaanalyses the sensitivity and specificity of MS-CT in detection of ISR achieved 90% and 91%, with positive and negative predictive value of 68% and 98%, respectively 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…As non-invasive MS-CT coronarography was used in control group to confirm the stents patency, it is not possible to avoid completely potential false negatives findings. However, in previous studies, MS-CT coronarography revealed sufficient accuracy for ISR detection 6,7 .…”
Section: Limitationsmentioning
confidence: 99%
“…Sun [36] and Kumbhani [37] in their study described the advantages of MS-CT in detecting stent coronary restenosis (nearly 1400 and 1500 evaluated stents).…”
Section: Matrix Metalloproteinases Mmp-3 and Mmp-9 As Predictors Of Imentioning
confidence: 99%